2013
DOI: 10.1007/s00432-013-1478-1
|View full text |Cite
|
Sign up to set email alerts
|

Relative and disease-free survival for breast cancer in relation to subtype: a population-based study

Abstract: Our population-based findings confirm that subtype is an independent prognostic factor for BC. Triple-negative and HER2-enriched subtypes would benefit from the development and wide application, respectively, of targeted treatments, which would also improve survival for younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 30 publications
5
25
0
Order By: Relevance
“…The Italian study reported that the survival of breast cancer patients with triple negative and HER2-enriched had lower survival rates than patients with other molecular subtypes (Minicozzi et al, 2013). Our findings are also supported by a study of breast cancer in black women, which found that triple negative and HER2-enriched patients had the lowest survival 5-year survival rates (Ihemelandu et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…The Italian study reported that the survival of breast cancer patients with triple negative and HER2-enriched had lower survival rates than patients with other molecular subtypes (Minicozzi et al, 2013). Our findings are also supported by a study of breast cancer in black women, which found that triple negative and HER2-enriched patients had the lowest survival 5-year survival rates (Ihemelandu et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…Our results, in terms of high percentage of HER2 positive tumors among de novo metastatic BC (27.5%), are consistent with those reported in literature, [17][18][19] confirming the tendency of this subtype to be more aggressive and to rapidly spread to distant sites. Furthermore, in the period 2006-2009, among 30 patients with HER2 positive BC, 6 cases were diagnosed with brain metastasis (20%).…”
Section: Discussionsupporting
confidence: 93%
“…Tumor stage pT4, pN2-pN3 and biological factors such as HER2 positivity and triple negativity are indicated as the most relevant prognostic factors to classify patients at high risk of disease progression. These choices are in agreement with literature data showing that pathological stage and intrinsic breast cancer subtypes are the most relevant prognostic factors able to influence clinical outcome [31], [32], [33], [34]. Interestingly, van Hezewijk et al [8], using a web-based 29-item questionnaire, reported that 130 respondents of different disciplines (surgeons, medical oncologists, radiation oncologists and nurse practitioners) identified as patients at high risk to follow-up with a higher frequency of visits those of younger age and with pT3-4/pN2-3 tumor, not taking into account tumor biology, as medical oncologists did in the present study.…”
Section: Discussionsupporting
confidence: 91%